2021
DOI: 10.1097/fjc.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes-Mediated LncRNA ZEB1-AS1 Facilitates Cell Injuries by miR-590-5p/ETS1 Axis Through the TGF-β/Smad Pathway in Oxidized Low-density Lipoprotein-induced Human Umbilical Vein Endothelial Cells

Abstract: Atherosclerosis is a chronic lipid-induced inflammation of the vessel wall. Oxidized low-density lipoprotein was confirmed to drive the onset of atherogenesis. Zinc finger e-box–binding homeobox 1 antisense 1 (ZEB1-AS1) is a long noncoding RNA that is involved in human diseases, including atherosclerosis. In this study, the role of exosomes-mediated ZEB1-AS1 and its underlying mechanisms in atherosclerosis were explored in oxidized low-density lipoprotein (ox-LDL)-treated human umbilical vein endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Contradictorily, a study of miRNA expression profile has shown that miR-590-5p is overexpressed in squamous cell carcinoma and functions as the tumor promoter [ 23 ]. In addition, miR-590-5p is downregulated in oxidized low density lipoprotein- (ox-LDL-) induced HUVECs, and the overexpression of miR-590-5p inhibits the apoptosis of HUVECs induced by ox-LDL [ 24 ]. In this study, we found that miR-590-5p overexpression promoted cell proliferation and induced cell apoptosis in A β -induced BV-2 and HT22 cells, which suggested that miR-590-5p exhibited protective effect against cell injury induced by A β .…”
Section: Discussionmentioning
confidence: 99%
“…Contradictorily, a study of miRNA expression profile has shown that miR-590-5p is overexpressed in squamous cell carcinoma and functions as the tumor promoter [ 23 ]. In addition, miR-590-5p is downregulated in oxidized low density lipoprotein- (ox-LDL-) induced HUVECs, and the overexpression of miR-590-5p inhibits the apoptosis of HUVECs induced by ox-LDL [ 24 ]. In this study, we found that miR-590-5p overexpression promoted cell proliferation and induced cell apoptosis in A β -induced BV-2 and HT22 cells, which suggested that miR-590-5p exhibited protective effect against cell injury induced by A β .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ZEB1-AS1 was also observed to participate in the endothelial injury induced by oxLDL with its increasing expression dose-independently and the further increasing levels of ROS and MDA, through the upregulating HMGB1 with the sponge of miR-942 and contributes to the apoptosis of endothelial cells ( 30 ). The exosome-mediated ZEB1-AS1 was also shown to facilitate cellular injury via signaling mediated with miR-590-5p and ETS1, and the pathway with TGF-β and Smad participated in oxLDL induced HUVECs ( 31 ). The inhibition of NEAT1 and the myocardial infarction-associated transcript (MIAT) expression in the oxLDL-induced model had also been reported to repress the endothelial dysfunction while their molecular pathways are quietly different.…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…Ni et al discussed the relationship between exocrine-derived non-coding RNAs (lncRNAs and miRNAs) in endothelial cells and vascular smooth muscle cells and their mechanism in vascular senescence (39). Recently, Cheng et al found in vitro that the exo-lncRNA ZEB1-AS1 secreted by human umbilical vein endothelial cells induced by oxidized low-density lipoprotein (ox-LDL) enhances the damage caused by the MIR-590-5P/ETS1 axis to human umbilical vein endothelial cells through the TGF-β/Smad pathway (40). Current studies have shown that exosomal lncRNAs participate in the dynamic evolution of underlying cardiovascular diseases through various pathways, involving all aspects of their pathophysiology and potential treatment.…”
Section: Exosomal Lncrna In Cardiovascular Diseasementioning
confidence: 99%